Carte du havre de Saint Jean dans l'Isle de Terre-neuve - Bellin, Jacques Nicolas, 1703-1772 ([Paris], 1764)
Black and white. North arrow with rhumb lines. North oriented to left. Decorative title cartouche. Relief shown pictorially. Depths shown by soundings. Shows rocks beneath the water. Bar scale in toises. Shows buildings.